The Development of Matriculation Chemistry Module: Needs Analysis - Ghani, Nor Syatilla Haerany Abd; Lee, Tien Tien (CENTRAL ASIA AND THE CAUCASUS, 2022)
The needs analysis study was conducted to obtain information from matriculation chemistry students and lecturers about 1) the problems encountered by the students and lecturers during the teaching and learning of matriculation chemistry subject, 2) the most challenging topics in matriculation chemistry syllabus and 3) the needs for the development of the teaching and learning module. This needs analysis study is a survey study involving 127 first semester matriculation students and eight matriculation lecturers selected by random sampling technique. Questionnaire was used as instrument for this study. It was divided into four parts: demographics, matriculation chemistry problems, matriculation chemistry topics difficulty level and suggestions to facilitate the learning of difficult chemistry topics. The results showed that matriculation chemistry is difficult because the subject is abstract. Besides that, feedback on the difficulty of matriculation chemistry topics showed the most difficult topic is the chemical bonding. Therefore, there is a need to develop a module that can be used as supporting materials in the teaching and learning of chemistry for matriculation students. In conclusion, students and lecturers need teaching and learning aids in chemical bonding topic to improve student’s understanding. The implication of the findings provided references to the development of effective teaching and learning module.